Modified MVR-CORDIC Algorithm and it’s Application in Attitude Measurement - Jiang Haitao; Shang Xiaoxing (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Aiming at attitude measurement with 51 MCU, The speed and efficiency of basic MVR-CORDIC (Modified Vector Rotational-Coordinate Rotation Digital Computer) are lower, we lists the steps used to measure the heading in rotate mode. Considered the features of the 51-MCU and the MVR-CORDIC algorithm, some new schemes about iteration number and searching algorithm are presented to improve the speed. this modified algorithm is tested and compared in 51-MCU, the experiment result shows that adaptive iteration makes iteration times to 67 percents of the general numbers and the modified searching algorithm reduces 57 percents of the normal iteration time. The experimental results show that the Angle indicator system has high resolution; accuracy of pitch Angle within the ±0.4°; the accuracy of roll within the ±0.4° when pitch angle is not more than 80°, which meet the measuring system accuracy. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2180